No Influence of Positive Emotion on Orbitofrontal Reality Filtering: Relevance for Confabulation - Liverani, Maria Chiara; Manuel, Aurélie L.; Guggisberg, Adrian G.; Nahum, Louis; Schnider, Armin (Frontiers in Behavioral Neuroscience, 2016)
Orbitofrontal reality filtering is a mechanism that allows us to keep thought and behavior in phase with reality. Its failure induces reality confusion with confabulation and disorientation. Confabulations have been claimed to have a positive emotional bias, suggesting that they emanate from a tendency to embellish the situation of a handicap. Here we tested the influence of positive emotion on orbitofrontal reality filtering in healthy subjects using a paradigm validated in reality confusing patients and with a known electrophysiological signature, a frontal positivity at 200-400 ms after memory evocation. Subjects made two continuous recognition tasks (“two runs”), composed of the same set of neutral and positive pictures, but arranged in different order. In both runs, participants had to indicate pictures repetitions within, and only within, the ongoing run. The first run measures learning and recognition. The second run, where all items are familiar, requires orbitofrontal reality filtering to avoid false positive responses. High-density evoked potentials were recorded from nineteen healthy subjects during completion of the task. Performance was more accurate and faster on neutral than positive pictures in both runs and all conditions. Evoked potential correlates of emotion and reality filtering occurred at 260-350 ms but dissociated in terms of amplitudes and topography. In both runs, positive stimuli evoked a more negative frontal potential than neutral ones. In the second run, the frontal positivity characteristic of reality filtering was separately, and to the same degree, expressed for positive and neutral stimuli. We conclude that orbitofrontal reality filtering, the ability to place oneself correctly in time and space, is not influenced by emotional positivity of the processed material.